Association between maternal occupational exposure to cleaning chemicals during pregnancy and childhood wheeze and asthma - Herrin, Melissa A.; Sherris, Allison R.; Dearborn, Logan C.; Loftus, Christine T.; Szpiro, Adam A.; Moore, Paul E.; Adgent, Margaret A.; Barrett, Emily S.; Nguyen, Ruby H. N.; Carroll, Kecia N.; Karr, Catherine J. (Frontiers in Epidemiology, 2023)
Asthma is a leading cause of childhood morbidity in the U.S. and a significant public health concern. The prenatal period is a critical window during which environmental influences, including maternal occupational exposures, can shape child respiratory health. Cleaning chemicals are commonly encountered in occupational settings, yet few studies have examined the potential link between prenatal occupational exposures to cleaning chemicals and risk of childhood wheeze and asthma. We evaluated the potential influence of maternal occupational exposure to cleaning chemicals during pregnancy on pediatric asthma and wheeze at child age 4 - 6 years in 453 mother-child pairs from two longitudinal pregnancy cohorts, TIDES and GAPPS, part of the ECHO prenatal and early childhood pathways to health (ECHO-PATHWAYS) consortium. Maternal occupational exposure to cleaning chemicals was defined based on reported occupation and frequency of occupational use of chemicals during pregnancy. Child current wheeze and asthma outcomes were defined by parental responses to a widely-used, standardized respiratory outcomes questionnaire administered at child age 4 – 6 years. Multivariable Poisson regression with robust standard errors was used to estimate relative risk (RR) of asthma in models adjusted for confounding. Effect modification by child sex was assessed using product interaction terms. Overall,116 mothers (25.6%) reported occupational exposure to cleaning chemicals during pregnancy, 11.7% of children had current wheeze, and 10.2% had current asthma. We did not identify associations between prenatal exposure to cleaning chemicals and current wheeze (RRadjusted 1.03, 95% confidence interval (CI): 0.56, 1.90) or current asthma (RRadjusted 0.89, CI: 0.46, 1.74) in the overall sample. Analyses of effect modification suggested an adverse association among females for current wheeze (RR 1.82, CI: 0.76, 4.37), compared to males (RR 0.68, CI: 0.29, 1.58), though the interaction p-value was >0.05. We did not observe evidence of associations between maternal prenatal occupational exposure to cleaning chemicals and childhood wheeze or asthma in the multi-site ECHO-PATHWAYS consortium. We leveraged longitudinal U.S. pregnancy cohorts with rich data characterization to expand on limited and mixed literature. Ongoing research is needed to more precisely characterize maternal occupational chemical exposures and impacts on child health in larger studies.